The use of cross-sectional echocardiography in a general hospital. Issue 654 (April 1980) - Brown, A. K.; Anderson, V.
Abstract : Three hundred and five patients routinely referred to a general hospital were surveyed to assess the advantages of cross-sectional echocardiography (CSE) over the conventional M mode method. CSE provided a dynamic display of the movement of the heart, particularly left ventricular function, and facilitated the location of cardiac structures. It was valuable in assessing the degree of mitral stenosis and the type of left ventricular outflow obstruction. Mitral valve prolapse, pericardial effusion, intracardiac tumours and congential heart disease were more easily diagnosed than by M mode techniques, but the origin of the basal systolic murmur still remained a problem. It was concluded that the 2 systems were complementary, and that CSE provided important additional information which improved the diagnostic capability of echocardiography.